ALTERATION IN TESTICULAR MORPHOLOGY AND SPERM COUNT DUE TO GLYCOWITHANOLIDES TREATMENT DURING AGING - Shaikh, Nilofar H; Deshmukh, Vidya M; Walvekar, Madhuri V (Asian Journal of Pharmaceutical and Clinical Research, 2015)
altered testicular morphology and reduced sperm count during aging. Methods: For this purpose, adult male mice (Mus musculus) of 6 months old, weighing 50-55 g were divided into following four groups viz. control Group (I), D-galactose treated Group (II), protective Group (III) and curative Group (IV). The effect of glycowithanolides (20 mg/kg body weight) was evaluated against aging. The body weight was recorded before and after treatment. Testes, epididymis, and seminal vesicle were collected, cleaned, and weighed and also were used for histopathological study. Epididymal sperm count was done. Results: The current study demonstrated that male mice receiving D-galactose caused a significant decrease in sperm count, body weight, weight of testes, epididymis, and seminal vesicle as compared to control (Group I) which was significantly increased in both protective (III) curative Group (IV). Histological studies of the testes revealed anti-spermatogenic effects of D-galactose reflected by a significant decrease in number of spermatogonia, spermatocytes, spermatids and leydig cells in the mice treated with D-galactose. In case of epididymis and seminal vesicle also showed marked destructive morphological changes. Histological structure which was returning back to normal as that observed in the control group (I) mice. Conclusion: Glycowithanolides enhance antioxidant system which consequently reduced oxidative stress in mice. The beneficial effect of glycowithanolides (WSG) is thus potentially reducing reproductive dysfunction and tissue damage. Keywords: Glycowithanolides, D-galactose, Sperm count, Testes, Epididymis and seminal vesicle.